Theoretical questions of environmental harm. (Journal of actual problems of jurisprudence, 2016)
In this article are considered concept of ecological harm by the modern legislation of RK. An author in this article examines the rule of international obligation in industry of the use of natural resources. And also, an author analyses providing of help in the period of the extraordinarily ecological state in a region. An author investigates priorities of participation of rules and norms of international law in industry of steady development of international initiatives.
Keywords: international contract; international relation